The Impact of Faculty Empowerment on Organizational Learning Effectiveness - Turi, Jamshid Ali; KhasKhelly, Farhan Zeb; Riaz, Sakina; Shaikh, Sadia (Institute of Gender Studies, University of Sindh, Jamshoro, Pakistan, 2019)
The study focuses on the employee empowerment and job satisfaction in the Universities of Pakistan. The methodology involved the data collection through survey questionnaires using random sampling technique from the faculty members in the Universities in Pakistan. SPSS was used for analyzing data and concluding results. Instrument reliability was pre-tested and reliability analysis were also conducted through Cronbach Aloha. Moreover, Independent T-test, ANOVA, regression and correlation analysis of the data was tested. The results show significant impact of the gender of the person on overall performance, empowerment upon the overall performance of the faculty in the learning organization like university in Pakistan.